1995
DOI: 10.1111/j.1432-1033.1995.tb20632.x
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharide Chain of Lupin Seed Conglutin gamma is not Responsible for the Protection of the Native Protein from Degradation by Trypsin, but Facilitates the Refolding of the Acid-Treated Protein to the Resistant Conformation

Abstract: Native glycosylated and enzymically deglycosylated conglutin gamma (a lupin seed oligomeric protein) both showed an unusual resistance to tryptic degradation. The result of this treatment was that a single 40-residue peptide was cleaved from the N-terminus of conglutin gamma light subunit. Acid treatment of the two protein forms led to their substantial unfolding, as indicated by CD spectra. After this treatment, both polypeptides were completely degraded by trypsin after a few minutes of incubation. Conversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Furthermore, it has been shown that c-conglutin is not affected by various intestinal and exogenous proteolytic enzymes under neutral or slightly acidic pH conditions, while the protein denatured and became fully susceptible at extreme pH values (Capraro et al, 2009). Nevertheless, the intrinsic resistance of the protein is quickly restored once c-conglutin is renatured at neutral/slightly alkaline pH values (Duranti, Gius, Sessa, & Vecchio, 1995). In our experiments, incubations with cells and tissues were conducted at neutral pH values and even lysosomal pH is not acidic enough to unfold the lupin protein in order to make it more susceptible to proteolysis.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, it has been shown that c-conglutin is not affected by various intestinal and exogenous proteolytic enzymes under neutral or slightly acidic pH conditions, while the protein denatured and became fully susceptible at extreme pH values (Capraro et al, 2009). Nevertheless, the intrinsic resistance of the protein is quickly restored once c-conglutin is renatured at neutral/slightly alkaline pH values (Duranti, Gius, Sessa, & Vecchio, 1995). In our experiments, incubations with cells and tissues were conducted at neutral pH values and even lysosomal pH is not acidic enough to unfold the lupin protein in order to make it more susceptible to proteolysis.…”
Section: Discussionmentioning
confidence: 98%
“…Lupin proteins have been analyzed by a number of different techniques, including liquid chromatography (Duranti et al, 1995), differential sedimentation (Franco et al, 1997;Freitas et al, 2000), proteomic analysis by one-and two-dimensional gel electrophoresis (Duranti et al, 1992;Magni et al, 2005b) or liquid chromatography/electrospray ionization tandem mass spectrometry (Schwend et al, 2003;Wait et al, 2005;Magni et al, 2007), isoelectrofocusing (Quaresma et al, 2007), crystallization (Biesiadka et al, 1999), and expression of recombinant protein (Scarafoni et al, 2001).…”
Section: Lupin Allergensmentioning
confidence: 99%
“…However, it has been shown that the in vitro allergenicity to lupins (L. albus) is reduced when an instantaneous controlled pressure drop is applied on lupin cotyledons (Guillamón et al, 2008). Additionally, other factors influencing lupin protein stability, such as saccharide chains (Duranti et al, 1995), the pH (Duranti et al, 2000), and the presence of metal ions (Ferreira et al, 1999;Duranti et al, 2002), have been examined. On the other hand, novel procedures to maintain the native protein properties have been proposed (W€ asche et al, 2001;D'Agostina et al, 2006), which certainly also entail conservation of lupin allergenicity.…”
Section: Effects Of Food Processingmentioning
confidence: 99%
“…Unlike the case of mammalian glycoproteins, in plant glycoproteins, the role of glycans in the folding and stability depends on the characteristics of individual protein [19][20][21][22]. In vitro studies have shown that once the protein is folded, glycosylation is often important for its stability [23][24][25].…”
Section: Introductionmentioning
confidence: 98%